Legal Protection of Notary Employees in the Judicial Process Against Forgery of Signatures of Confrontants on Authentic Deeds - Aprianto, Aprianto; Tarsono, Edi; Satrio, Yoga (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2025)
Notaries are public officials authorized by law to draw up authentic deeds and are formally responsible for ensuring the accuracy of the parties' identities, the contents of the deed, and the signatures affixed. This study examines the legal protection available to notary staff who act as witnesses in the preparation of deeds, particularly in criminal proceedings involving forged signatures by parties appearing before the notary. Using a normative juridical method with a descriptive approach, the research analyzes secondary data obtained through document studies, including legislation, literature, and court decisions. The case analyzed is the Indonesian Supreme Court Decision No. 1209 K/Pid/2022, in which the notary was found guilty of initiating and participating in document forgery and sentenced to one year and six months of imprisonment. The findings indicate that notary staff who are not involved in the forgery are not subject to criminal liability. This research contributes to the discourse on legal accountability in notarial practice and emphasizes the importance of providing clearer legal safeguards for notary employees.